PENGARUH AGGRESIVITAS PAJAK, KEPEMILIKAN KELUARGA DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR TAHUN 2012-2014 - Ernie Riswandari (Jurnal Akuntansi Bisnis, 2017)
This study examined the policy of the variables affecting debt is aggresivitas tax enterprises.At the family ownership and the size of the manufacturing companies listed in Indonesia Stock Exchange in 2012-2014 . This research is a quantitative study using regression test is intended to test the effect of independent variables on the dependent variable. Based on these data and if the data that has been done shows that the family ownership has a positive and significant impact on the debt policy. While aggresivitas tax and company size affect positively but not significant.Key Word : debt policy , family ownership, tax aggressiveness, the size of the company